Вразливості месенджерів «TELEGRAM», «WHATSAP», «VIBER» - Пашнєва, О. Р. (ХНУРЕ, 2024)
The proliferation of messaging applications such as Telegram, WhatsApp, and Viber has revolutionized communication, but it has also introduced a myriad of security concerns. This paper provides a analysis of the vulnerabilities present in the messengers Telegram, WhatsApp and Viber, with a particular focus on the threat of phishing attacks. As these platforms handle sensitive personal and professional information, they are increasingly becoming prime targets for attackers who seek to exploit unsuspecting users through deceptive tactics. The relevance of this research is due to the increasing use of these messengers for communication in various domains, including business, personal, and government.
Keywords: месенджер «TELEGRAM»; месенджер «WHATSAP»